The Concept of ‘Human Dignity’ in the Post-War Human Rights Debates (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The paper explores early post-war human rights language by looking at the drafting of the first article of the Universal Declaration of Human Rights (1948), with a focus especially on the concept of ‘dignity’. ‘Human dignity’ has been regarded as a central, even undisputable concept in discourse related to human rights since the Second World War. The first article of the Universal Declaration of Human Rights states how “All human beings are born free and equal in dignity and rights. They are endowed with reason and conscience and should act towards one another in a spirit of brotherhood”. By looking at the preparatory work on the first article, and the related political choices and conceptual disputes, the paper will emphasise the political and rhetorical character of the concept of ‘human dignity’.